Report on the third International Martial Arts and Combat Sports Scientific Society (IMACSSS) Conference - Dominique Brizin (Universidad de León, 2015)
The present report provides a brief account of the Conference "Man - Martial Arts - Humanism", held by the International Martial Arts and Combat Sport Scientific Society (IMACSSS) on October 15th - 17th, 2014 in Rzeszów, Poland. During this international conference, scientists from various universities presented their actual projects and results of their latest projects in the field of martial arts and combat sports (MA&CS). Subjects covered a wide range, starting with anthropology, sociology, history, philosophy, psychology, reaching up to pedagogy and didactic methodology, bio-technical approaches and theoretical structures in MA&CS. The conference drew more than 120 participants and contributed to the formation of a close network in the community of the scientists conducting research within the field of MA&CS.